A century and three‐quarters of Bank Rate and long‐term interest rates in the United Kingdom. (March 2017) - Berument, Hakan; Cabezon, Ezequiel; Froyen, Richard
Abstract: Over the years from 1844 to 2013, the United Kingdom had several distinct monetary policy regimes. This paper examines the relationship between the Bank of England policy rate and UK long‐term rates in each regime. Our starting point is R. G. Hawtrey's A century of Bank Rate, which focused mainly on the classical Gold Standard. We also examine the Interwar years, post‐Second World War years of policy by discretion and the recent regime of inflation targeting. We find that policy regimes that firmly anchor inflationary expectations result in long‐run interest rates becoming less responsive to changes in monetary policy rates. This suggests a conflict between a regime that anchors inflationary expectations and one that allows a central bank to have significant effects on long‐term rates via a short‐term policy rate.